2008
DOI: 10.1007/s10695-008-9260-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the estrogen mimic genistein as a dietary component on sex differentiation and ethoxyresorufin-O-deethylase (EROD) activity in channel catfish (Ictalurus punctatus)

Abstract: A number of aquaculture species, including channel catfish Ictalurus punctatus, are fed high proportions of soybean meal in their diet. We have investigated the potential for the most common phytoestrogen in soybean meal to alter phenotypic sex during sexual differentiation in channel catfish. Channel catfish were fed four dietary concentrations of the phytoestrogen genistein (0, 2, 4, and 8 mg g(-1)) to determine its effect on gonadal sex differentiation. The four treatment diets were fed to sexually undiffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 38 publications
0
34
1
Order By: Relevance
“…Genistein can have both estrogenic and antiestrogenic effects, either of which, in turn, can have stimulatory or suppressive actions on growth and reproduction in fish (Green and Kelly, 2009). In the present study, fish fed genistein supplemented diet showed no significant change in growth (P>0.05) compared to the control fish.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Genistein can have both estrogenic and antiestrogenic effects, either of which, in turn, can have stimulatory or suppressive actions on growth and reproduction in fish (Green and Kelly, 2009). In the present study, fish fed genistein supplemented diet showed no significant change in growth (P>0.05) compared to the control fish.…”
Section: Discussioncontrasting
confidence: 51%
“…Genistein was added to finely ground diets (crude protein 35.4%) using 10 ml of a 1:1 mixture of dimethylsulfoxide (DMSO) and ethanol for 1 kg feed (Green and Kelly, 2009) while methanol extract of B. alba was added after dissolving in DMSO only (Moundipa et al, 2005). Control diet was treated with a 1:1 mixture of DMSO and ethanol only.…”
Section: Preparation Of Experimental Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may enter the aquatic environment from agricultural (Burnison et al 2003; Hartmann et al 2008; Kolpin et al 2010) and industrial sources (Lundgren and Novak 2009) and may disrupt reproductive endocrine function. For example, TO have been induced in fishes through both aqueous (Kiparissis et al 2003) and dietary (Green and Kelly 2009) exposures to selected phytoestrogens.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of natural carcinogens and anticarcinogens in plants and other dietary factors are now well characterized in research focused on optimization of healthy aging (Aiyer et al 2008; Akhtar et al 2009). Recently dietary factors such as trace contamination by arsenic and other metals (Kozul et al 2008) and estrogenic plant components in practical laboratory animal diets (Adlercreutz 2007; Adlercreutz et al 2004; Cross et al 2004; Green and Kelly 2008; Ziegler et al 2004) have been recognized as confounding factors in toxicology and carcinogenesis studies.…”
Section: Introductionmentioning
confidence: 99%